Peningkatan Upaya Preventif Kesehatan Remaja melalui Screning dan Konseling Diabetes Mellitus - Asnuddin, Asnuddin; Roni, Roni; Arsad, Arsad; Pratiwi, Wilda Rezki (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Adolescence is a critical phase of life marked by significant physical, emotional, and social changes, which increase vulnerability to health issues such as Type 2 Diabetes Mellitus (DM). The rising incidence of DM among young people is influenced by poor dietary habits, lack of physical activity, and unhealthy lifestyles. Unfortunately, adolescents often lack awareness about the risks and consequences of DM. To address this, a community service initiative was conducted involving health screening and counseling on DM management and prevention using educational flipcharts. This activity aimed to detect early risk factors and enhance adolescents' understanding of how to independently manage and prevent DM. Evaluation results indicated a significant improvement in knowledge (p-value 0.003 0.05), demonstrating that counseling had a positive impact on adolescents' awareness and comprehension of diabetes management and prevention.